The Decolonial Mandela : Peace, Justice and the Politics of Life. - Ndlovu-Gatsheni, Sabelo J. (Berghahn Books, 2016)
A significant contribution to the emerging literature on decolonial studies, this concise and forcefully argued volume lays out a groundbreaking interpretation of the 'Mandela phenomenon.' Contrary to a neoliberal social model that privileges adversarial criminal justice and a rationalistic approach to war making, Sabelo J. Ndlovu-Gatsheni identifies transformative political justice and a reimagined social order as key features of Nelson Mandela's legacy. Mandela is understood here as an exemplar of decolonial humanism, one who embodied the idea of survivor's justice and held up reconciliation and racial harmony as essential for transcending colonial modes of thought.